The effects of receptive and expressive instructional sequences on varied conditional discriminations. Issue 4 (21st August 2017) - Bao, Shimin; Sweatt, Kristin T.; Lechago, Sarah A.; Antal, Sarah
Abstract : Many Early Intensive Behavioral Intervention (EIBI) curricula recommend teaching receptive responding before targeting expressive responding (Leaf & McEachin, 1999; Lovaas, 2003). However, a small literature base suggests that teaching expressive responses first may be more efficient when teaching children with ASD and other developmental disabilities (Petursdottir & Carr, 2011). The present study employed an alternating treatments design to compare the effects of three instructional sequences to teach feature, function, and class to three children diagnosed with ASD: (a) receptive–expressive, (b) expressive–receptive, and (c) mixed. The results suggested that expressive–receptive was the most efficient training sequence for all three participants. Additionally, greater emergent responding was observed with the expressive–receptive training sequence.